Penguatan Kapasitas Kelompok Masyarakat Melalui Pembuatan Bibit Stek Batang Loa (Ficus rasemosa) di Desa Cimara Kabupaten Kuningan - Yayan Hendrayana; Toto Supartono; Ilham Adhya; Nina Herlina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Kuningan, 2026)
The problem of degraded land that has the potential to experience environmental deterioration due to erosion and the decline of natural vegetation cover occurs in Cimara Village, Kuningan Regency. This condition can lead to reduced soil fertility and a decline in ecosystem functions in maintaining environmental balance. One effort that can be undertaken to improve this condition is land rehabilitation by utilizing local tree species such as loa (Ficus racemosa), which is known for its high adaptability to local environmental conditions and its important role in reducing soil erosion. This community service activity aims to provide training to the local community on techniques for producing seedlings through the stem cutting method of kiara karasak, which is expected to support sustainable land rehabilitation programs. The implementation methods include an introduction to the kiara karasak plant, training on selecting healthy and suitable stems for cuttings, proper cutting techniques, the use of root growth hormones, as well as seedling propagation and maintenance to ensure optimal growth. The approach used in this activity is participatory, involving direct field practice so that participants can understand and independently apply each stage of the process. During the training, participants were also provided with knowledge on seedling maintenance techniques until the seedlings are ready to be planted in rehabilitation areas. The results of the activity indicate a significant improvement in participants’ understanding and technical skills in producing seedlings through stem cuttings. Participants are now better prepared to produce loa tree seedlings independently and actively contribute to land rehabilitation efforts in Cimara Village. This activity is expected to generate long-term positive impacts on environmental quality improvement while also increasing community awareness of the importance of maintaining ecosystem sustainability in the area.